On the Wallachian frontiers: colonization and directions of migration of the Wallachian population in the Silesian-Kysuce-Moravian borderland (in the light of historiography) - Nowak, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2022)
The article discusses the historiography of the problem of the history and directions of migration of Wallachian settlers who came to the geographical border of Silesia, Kysuce and Moravia, i.e. the historical and political border between Poland, the Czech Republic and Hungary in the first half of the 16th century. These matters have aroused and aroused controversy for many years. This area was the end point of the Wallachians’ wanderings to the west and therefore there was a lot of confusion as to where they came from and where they traveled. The most documented scientific publication on this subject is still the work of the Czech researcher Josef Macůrek from 1959, so from (unfortunately) more than 60 years ago.